Groundwater Exploration in Tirtoadi using the Geoelectric Schlumberger Method - Zakaria, Muhammad Faizal; Handayani, Tira Khasanah (RSF Conference Series: Engineering and Technology, 2022)
Tirtoadi sub-district is one of the areas mentioned as being on alert for meteorological drought, which is a condition of not experiencing a day without rain (HTH) for more than 60 days. This research aims to provide information on the presence of subsurface water using geoelectric methods. Data acquisition was carried out at 20 points in Tirtoadi. The distribution of points is random but evenly distributed in the research area. The equipment used is Syscal Jr and the measuring range is 600 m AB, and the direction of the stretch is relatively north to south. The field data obtained are deltas V and I. These data are used to calculate R and Rho. The resistivity value obtained is the apparent resistivity. To obtain a subsurface model of the actual resistivity, it is necessary to perform a 1-D inversion. The inversion is carried out using the Progress V3.0 software. The results obtained in this study are variations in the value of subsurface resistivity. Resistivity of water-containing aquifers ranges between 10 ?m – 50 ?m. The depth of groundwater varies between 50 meters to 80 meters. The thickness of the groundwater varies between 5 meters to 22 meters. The recommended drill point is given at T11 with coordinates 49 S 424996 N 9144372 E because at this point it has the shallowest depth and thick enough thickness.